2013
DOI: 10.1590/s2317-17822013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Diagrama de desvio fonatório e análise perceptivo-auditiva pré e pós-terapia vocal

Abstract: OBJETIVO: Verificar se o Diagrama de Desvio Fonatório (DDF) demonstra a mudança vocal obtida por meio da terapia fonoaudiológica e se acompanha as alterações da análise perceptivo-auditiva. MÉTODOS: Foram analisadas amostras da vogal sustentada /ε/ de 34 indivíduos, com diversos tipos de disfonia, nos momentos pré e pós-terapia. As vozes foram submetidas à análise acústica pelo DDF e perceptivo-auditiva pela escala analógica visual (EAV) de 100 pontos. No DDF, as vozes foram classificadas quanto à densidade (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
1
16
1
10
Order By: Relevance
“…Such fact may be explained by the number of voices of the normality quadrant in the control group out. Studies showed that pathological voices occupy specific regions in the diagram 10 and that more altered voices are found in the upper right quadrant 14,15 corroborating the findings observed in the present study. This author also found that breathy voices are located in the upper right quadrant, which was also verified in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such fact may be explained by the number of voices of the normality quadrant in the control group out. Studies showed that pathological voices occupy specific regions in the diagram 10 and that more altered voices are found in the upper right quadrant 14,15 corroborating the findings observed in the present study. This author also found that breathy voices are located in the upper right quadrant, which was also verified in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The diagram is based in four acoustic measures: three of them related to irregularity of the sound signal -jitter, shimmer and their correlation; the fourth one is related to the noise component, named glottal to noise excitation ratio -GNE [13][14][15] . The differential of this diagram is that it is able to assess very deviant voices, besides showing differences between dysphonic groups with different phonatory mechanisms and it allows monitoring of vocal quality 10,[13][14][15][16][17] . The GNE is the acoustic measure that calculates the noise produced by the oscillation of vocal chords.…”
Section: Methodsmentioning
confidence: 99%
“…Most voices were located at the quadrant 1, left lower; it is know that voices that are less deviated are closer to the quadrant 1 (22,23) , therefore, the voices of the children from this study, that were considered normal by the perceptual-auditory evaluation, also showed normal acoustic parameters.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies, with adults, have demonstrated concentrated density at post-therapy moment and a greater concentration of the points in voices with no or mild deviations (22,23) . The spread density observed in the present research may be a reflection of the children irregular vocal quality due to the immature vocal ligament.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation